Action Research to Develop Mathematical Learning Activities by Using Games - et. al., Uraiwan Pantachord, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of this research were 1) to design and develop mathematical learning activities by using games and 2) to study the results of mathematics learning activities by using games. There were two groups of population. The first group was the fourth year mathematics program with a number of 24 people who are responsible for the design and develop mathematical learning activities by using games. The second group consisted of 81 students in Mathayomsuksa 1, which were used to study the results of mathematics learning activities by using games. The research instruments were operational research processes, mathematics achievement test and the teamwork measures. The statistics used for data analysis were mean, standard deviation, t-test dependent and content analysis.